Beyond words a digital short on the importance of open communication in parent-adolescent relationships in Chinese Filipino Families - Hong, Jeiel Jireh C.
Chinese Filipinos have integrated themselves in Philippine society and are now mainly composed of local-born second, third, and fourth generation chinese who have evolved along with the changes that came in culture and environment. With this, the family dynamics in Chinese Filipino families have also notably changed. This thesis examined the effect of parent-adolescent relationships in Chinese Filipino families on the adolescent's self-esteem. The sample focused on Chinese Filipino families based in Metro Manila, specifically those who are considered Greenhills / Quezon City Chinese. Findings showed that even as these parents try to be more supportive and involved in their children's lives, conflict cannot be avoided. As children transition to adolescence, they develop different perspectives, values, beliefs, and opinions, and this gives rise to the need for open communication with their parents so that a better understanding and deeper relationship is developed. Based on conclusions made from this study, contemporary Chinese Filipino parents need to be aware of their role in their children's self-esteem during adolescence. The self-esteem of the child and how the parents contribute to this rely heavily on how they communicate their encouragement and support. To raise awareness and inspire parents in the community to get started on establishing a safe space for open communication, beyond words, a digital short to be released on the International day of Families, will be released via Chinoy TV, which is a Chinese Filipino media platform.